Acupuncture and Traditional Chinese Herbal Medicine Integrated With Conventional Rehabilitation for Post-stroke Functional Recovery: A Retrospective Cohort Study - Tseng, Cheng-Yu; Hsu, Pei-Shan; Lee, Chang-Ti; Huang, Hui-Fen; Lan, Chou-Chin; Hsieh, Tsung-Han; Liu, Guan-Ting; Kuo, Chan-Yen; Wang, Ming-Chieh; Hsieh, Po-Chun (Frontiers in Neuroscience, 2022)
Background: Stroke leads to tremendous impacts on patients and the healthcare system. It is crucial to explore the potential management of rehabilitation. Acupuncture and traditional Chinese herbal medicine (TCHM) integrated with conventional rehabilitation benefit post-stroke functional recovery. Methods: We retrospectively reviewed the medical records of all patients included in the Integrated Traditional Chinese-Western Medicine care program for stroke (ITCWM-stroke care program) in 2019 in Taipei Tzu Chi Hospital to investigate the effects of acupuncture and TCHM integrated with conventional rehabilitation on NIHSS and BI scores before and after the program. Results: A total of 255 stroke inpatients were retrieved and divided into acupuncture and acupuncture + TCHM group by hemorrhagic and ischemic stroke types, respectively. All the patients were recruited in the program at the early subacute phase after stroke onset. Of the hemorrhagic and ischemic stroke subjects, the NIHSS and BI total scores were significantly improved in the acupuncture and acupuncture + TCHM groups. The subgroup analysis results showed that in subjects with a baseline BI score ≤ 40, the acupuncture + TCHM group significantly improved BI total score better than the acupuncture group in both hemorrhagic (p < 0.05) and ischemic (p < 0.05) stroke subjects. Conclusions: Acupuncture and TCHM integrated with conventional rehabilitation significantly improve stroke patients’ functional recovery at the early subacute phase. Acupuncture + TCHM contributes to better activities of daily living (ADL) improvements in stroke patients with a baseline BI score ≤ 40. We suggest integrating acupuncture and TCHM into the post-stroke rehabilitation strategy, especially for stroke patients with poor ADL function.